2017
DOI: 10.1371/journal.pbio.2003404
|View full text |Cite
|
Sign up to set email alerts
|

Saccades are phase-locked to alpha oscillations in the occipital and medial temporal lobe during successful memory encoding

Abstract: Efficient sampling of visual information requires a coordination of eye movements and ongoing brain oscillations. Using intracranial and magnetoencephalography (MEG) recordings, we show that saccades are locked to the phase of visual alpha oscillations and that this coordination is related to successful mnemonic encoding of visual scenes. Furthermore, parahippocampal and retrosplenial cortex involvement in this coordination reflects effective vision-to-memory mapping, highlighting the importance of neural osci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 35 publications
8
71
0
Order By: Relevance
“…Beyond responses in theta rhythm, work using intracranial recordings in epileptic cases, as well as magnetoencephalography recordings in healthy participants, revealed that alpha oscillations in occipital, parietal, and temporal regions, including the parahippocampus, showed significantly higher phase‐locking for subsequently remembered, versus forgotten, trials during the time just before a saccade . Work continues to comprehensively outline the broad impact of eye movements on the coordination of distinct bands of neural oscillations within and across brain regions.…”
Section: Neurophysiology and Oscillatory Responsesmentioning
confidence: 99%
“…Beyond responses in theta rhythm, work using intracranial recordings in epileptic cases, as well as magnetoencephalography recordings in healthy participants, revealed that alpha oscillations in occipital, parietal, and temporal regions, including the parahippocampus, showed significantly higher phase‐locking for subsequently remembered, versus forgotten, trials during the time just before a saccade . Work continues to comprehensively outline the broad impact of eye movements on the coordination of distinct bands of neural oscillations within and across brain regions.…”
Section: Neurophysiology and Oscillatory Responsesmentioning
confidence: 99%
“…Saccades have been shown to modulate LFPs in multiple brain areas, such as PFC (Tremblay et al, 2015) and visual cortex (Ito et al, 2011(Ito et al, , 2013Staudigl et al, 2017) cortices. In V1, both saccades and fixations have been found to elicit PC in the delta/theta and alpha/beta bands (Ito et al, 2011(Ito et al, , 2013.…”
Section: Origin Of Lfp Modulationsmentioning
confidence: 99%
“…The hippocampus is known to play a critical role in associative memory formation and retrieval (Buffalo, ; Eichenbaum, ; Eichenbaum & Cohen, ; Schiller et al, ; Watrous & Ekstrom, ). Previous studies have shown that hippocampal neuronal activity is modulated around eye movement onsets in both human and nonhuman primates (Hoffman et al, ; Jutras, Fries, & Buffalo, ; Ringo, Sobotka, Diltz, & Bunce, ; Sobotka & Ringo, ; Staudigl, Hartl, Noachtar, Doeller, & Jensen, ). This modulation occurs in complete darkness (Sobotka & Ringo, ) or during rapid eye movement sleep (Andrillon, Nir, Cirelli, Tononi, & Fried, ), suggesting that it has an extra‐retinal origin.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations